Sustainability Learning and Cocoa Farmers’ Readiness for EUDR Compliance: Insights from a Desk Study in Indonesia - Muhammad Obie (Kirana Publisher (KNPub), 2026)
The European Union Deforestation Regulation (EUDR) introduces new sustainability requirements that significantly affect global cocoa supply chains. As one of the world’s major cocoa-producing countries, Indonesia faces considerable challenges in ensuring that smallholder farmers comply with EUDR provisions related to traceability, geolocation, and deforestation-free production. In this context, sustainability learning has emerged as a critical factor in strengthening farmers’ capacity to adapt to evolving environmental and market standards. This study examines the relationship between sustainability learning and cocoa farmers’ readiness for EUDR compliance through a desk study approach. Data were collected from scientific journal articles, policy documents, reports from international organizations, and government publications related to agricultural extension, sustainability education, digital literacy, and cocoa governance. The data were analyzed using thematic content analysis. The findings indicate that farmers’ readiness for EUDR compliance is strongly influenced by sustainability learning opportunities, the effectiveness of agricultural extension services, and the level of digital literacy required for traceability systems. Significant knowledge gaps regarding EUDR requirements remain, particularly among smallholders in remote areas. Strengthening sustainability-oriented extension programs, promoting digital learning platforms, and enhancing institutional support are essential for improving compliance readiness. This study contributes to the literature on sustainability education and offers policy insights for supporting cocoa farmers in meeting emerging global sustainability standards.